Android-Based Interactive Learning Multimedia to Improve Reading Literacy in High Schools - Faizal; Aunurrahman; Indri Astuti; Herry Sujaini; Urai Salam (Jurnal Edutech Undiksha, 2024)
Reading is the first skill to master in other literature. Students’ literacy is still low, according to PISA in 2018. There is a need for efforts to improve literacy skills, one of which is the development of literacy platforms. The aim of this research is to develop multimedia learning to improve reading literacy. Research and development (R&D) is based on the Dick & Carey development model. The study was conducted at senior high school, with 30 students participating. Multimedia is validated by material, design, and media experts. Data from the questionnaire instruments and student responses are analyzed with both qualitative and quantitative analysis. Overall, from the data analysis results, expert validation data was declared "very valid" with an average of 4.27. The results of an empirical test analysis with individual, small-group, and field trials stated the media was "very valid" and ready for use in learning, with an average of 4.66. From the results of the pretest and posttest involving 30 students, the result of the calculation of the t test obtained a value of 0,000, with the conclusion that there was a difference in the outcome of the pre-test and post-test. From the calculation of effect size with Cohen’s d, we get a value of 3.55 for category strong. Based on the results above, the Literacy Platform application developed can improve reading literacy and can be applied to learning.